Increased expression of the interleukin 1 receptor on blood neutrophils of humans with the sepsis syndrome. - Fasano, M B (1991)
Because of the potential importance of interleukin 1 (IL-1) in modulating inflammation and the observations that human blood neutrophils (PMN) express IL-1 receptors (IL-1R) and synthesize IL-1 alpha and IL-1 beta, we studied the IL-1R on blood PMN from a group of patients with the sepsis syndrome. We report a marked enhancement in the sites per cell of IL-1R expressed on sepsis-PMN of 25 consecutively studied patients compared to 20 controls (patient mean = 9,329 +/- 2,212 SE; control mean = 716 +/- 42 SE, respectively). There was no demonstrable difference in the Kd of IL-1R on sepsis-PMN (approximately 1 nM) as determined by saturation curves of 125I-IL-1 alpha binding and the IL-1R on sepsis-PMN had an apparent Mr approximately 68,000, a value like that of normal PMN. Cytofluorographic analysis indicated that the sepsis-PMN phenotype is a single homogeneous population with respect to IL-1R expression. In contrast, expression of the membrane complement receptor CR3 is not increased on sepsis-PMN. Similar increases in expression of IL-1R were not observed in various other inflammatory processes, including acute disseminated inflammation and organ failure not caused by infection, acute infection without organ failure, and immunopathologies such as active systemic lupus erythematosus and rheumatoid arthritis. Enhanced expression of IL-1R was not related simply to the state of myeloid stimulation. Increased expression of IL-1R on normal PMN was induced in vitro by incubating cells with recombinant human granulocyte-macrophage/colony-stimulating factor for 18 h and this response was inhibited by cycloheximide, suggesting the possibility that de novo synthesis of IL-1R might occur in PMN during the sepsis syndrome.